Botulinum toxin injection shows promise in nail psoriasis: A comparative randomized controlled trialCapsule Summary - Premjit Juntongjin, MD; Suthima Srisinlapakig, MD, MSc; Sunatra Nitayavardhana, MD (Elsevier, 2024)
Background: Nail psoriasis remains a challenging condition with limited satisfaction from current treatments. An increasing number of neuropeptides were reported in psoriatic tissue. Objective: To compare the efficacy of botulinum toxin A (BoNT-A) injection, triamcinolone acetonide (TA) injection, topical combination of vitamin D/steroid (VitD/steroid) and placebo in improving nail psoriasis. Methods: A 24-week randomized intraindividual comparative-controlled study involved participants with at least 4 psoriatic fingernails, each with a total target nail psoriasis severity index (NAPSI) score of at least 3 points. Nails were randomly received different treatments; intralesional BoNT-A injection at baseline, intralesional TA at baseline and eighth week, daily topical VitD/steroid application for 16 weeks and placebo. Results: Evaluation of 64 psoriatic fingernails showed a 40% reduction in the total target NAPSI score at 24 weeks following BoNT-A injection (P = .001). BoNT-A significantly improved nail bed lesions more than TA and topical VitD/steroid (P = .038), with no reported serious adverse effects. Limitations: Relatively small sample size; hand hygiene during the COVID-19 pandemic may interfere NAPSI score evaluation. Conclusions: BoNT-A injection emerges as a promising and effective therapy for nail psoriasis, providing sustained efficacy lasting up to 6 months with a single injection.